Fashion media consumption influence on the figure dissatisfaction and clothing interests of select older Filipina millennials - Lagrada, Jamie A.; Lumawig, Maria Josephine T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT The study is a descriptive survey that aimed to determine the influence of fashion media consumption to the figure dissatisfaction and clothing interests of select older Filipina Millennials. Specifically, its objective was to provide a fashion media consumption and figure perceptions profile of the respondents. It further aimed to identify relationships between the fashion media consumption and figure dissatisfaction, and fashion media consumption and clothing interests, of the respondents. The study utilized an online survey questionnaire, which was answered by 101 Filipina Millennials aged 25 to 35 years old conveniently selected through Snowball Sampling. The study showed that older Filipina Millennials‟ most consumed forms of fashion media were social networking sites. They were revealed to have a moderate exposure to their most consumed forms of fashion media with or without conscious effort to do so, and a low willingness to spend money on these forms of fashion media. Their self-perceived real figure was revealed to be one size bigger than the figure they considered ideal and the figure they wanted to achieve. Almost half of the respondents were found to have low figure dissatisfaction, with their top common figure issues being stomach and waist, weight, and arms. The top clothing interests displayed by the respondents were Comfort, Self-Enhancement, and Economy and Practicality. Fashion media consumption showed a negligible relationship with figure dissatisfaction. Meanwhile, it showed a moderate positive relationship with Aesthetics Satisfaction and Experimentation, a weak positive relationship with Self-Enhancement, Conformity, and Self-expression, and a negligible relationship with Comfort, Modesty, and Economy and Practicality. For future researches, the study recommends a more in-depth exploration of each of the variables of the study.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing and dress; Fashion